Study on therapeutic effectiveness of laparoscopic drainage and image guided pigtail catheter drainage in the treatment of liver abscess: a randomised controlled trial - Chitrambalam, Tharun Ganapathy; Pethuraj, Manimaran; S., Jeyakumar; Anguraj, Preetham (International Surgery Journal, 2019)
Background: Liver abscess is one of the major diseases of gastrointestinal system. A liver abscess is a suppurative cavity in the liver resulting from the invasion and multiplication of microorganisms, entering directly from an injury through the blood vessels or by the way of the biliary ductal system. Liver abscesses are most commonly due to pyogenic, amoebic or mixed infections. Methods: This is a randomised controlled trial to compare the outcomes of image guided pigtail catheter drainage and laparoscopic drainage in treatment of liver abscess. A total of 60 patients were recruited for the study and were divided into two groups between March 2017 to August 2018 with a follow up period of 6 months. Results: Mean average pain score were significantly higher in image guided pigtail drainage group than in laparoscopic drainage group on 2nd, 5th and 7th day. The time taken for more than 50% resolution and for total resolution of abscess cavity size in the laparoscopic drainage group is significantly less than the time taken by the pigtail drainage group (p value <0.001). The average duration of hospital stay with pigtail catheter drainage is significantly higher (14.5±2.03) than the average duration of hospital stays with laparoscopic drainage (8.07±0.78). Conclusions: We conclude that laparoscopic drainage of liver abscess is superior to image guided pigtail catheter drainage in terms of post-operative pain, hospital stay post procedure and resolution of abscess cavity.